The Impact of Ski Geometry Data and Standing Height on the Risk of Falling in Recreational Alpine Skiers - Gerhard Ruedl (MDPI AG, 2021)
The aim of this study was to evaluate the impact of individual, equipment-related and environmental factors associated with falls among adult recreational skiers. Individual, equipment-related (ski geometry data) and environmental data were collected by questionnaire among uninjured skiers with and without reported falls during the skiing day. Ski length, side cut radius, and width of the waist were directly recorded from the ski and standing height was measured using a digital sliding caliper. Absolute ski length was relativized to body height. A total of 1174 recreational skiers participated in this study, of whom 13.5% (n = 158) reported at least one fall during the skiing day. Results of the multiple logistic regression analysis found that a lower age, a very good/good fitness level, a moderate skiing speed, a lower relativized ski length, and fresh and grippy snow conditions decreased, while a lower skill level, a larger sidecut radius and an easy slope difficulty increased risk of falling on ski slopes. Besides individual and environmental factors, a lower relativized ski length and a lower sidecut radius decreased the risk of falling. Considering these ski geometry parameters when buying new skis could potentially decrease the risk of falling and thus prevent injuries in recreational skiers.